A comparative study of the antidepressant effect of ondansetron and granisetron on Albino mice - Shah, Mansi J.; M., Geetha; H. D., Rahul; G. H., Shashikala (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Ondansetron and granisetron are selective 5-HT receptor antagonists used as antiemetics. The present study as aimed at comparing the antidepressant activity of ondansetron and granisetron in animal experimental models. Methods: The study was done after obtaining approval from the institutional animal ethical committee of JJM Medical college, Davangere and CPCSEA. A total of 24 mice of either sex and of weight between 20-40g were included in the study. The antidepressant activity of ondansetron and granisetron was evaluated in mice using forced swim test model (FST) and tail suspension test model (TST). In both the experimental models animals were divided into 4 groups and received the following drugs- Group 1 (control) - normal saline 10mg/kg i.p, Group 2 (standard)-fluoxetine 10mg/kg i.p, Group 3(test drug 1), ondansetron 2mg/kg i.p, Group 4 (test drug 2)- granisetron 0.5mg/kg i.p. The duration of immobility was noted and compared amongst the 4 groups in both the models 60 min after drug administration. The observations were analysed using ANOVA (one way) and post hoc Tukey’s test. Results: The test drugs showed significant reduction in duration of immobility in both the models. In FST and TST models, granisetron (0.5mg/kg i.p) showed a significant reduction in immobility period of 10.33 sec and 67 secs respectively when compared to ondansetron (2mg/kg i.p) and the standard drug fluoxetine (10mg/kg i.p). Conclusions: The results of study suggest that granisetron may be useful as a potential candidate for treatment of depression. Hence further animal studies with different model for depression and clinical studies should be conducted in order to choose the better drug for treatment PONV which is often associated with depression.